Anthropometric Study of Orbitonasal Proportion and Their Comparisons in Bangladeshi Buddhist Rakhain Ethnic Males and Females (Journal of National Institute of Neurosciences Bangladesh, 2025)
Background: Anthropometric pattern of the orbitonasal proportion varies with no universal normative values.Objective: The purpose of the present study was to evaluate the anthropometric study of orbitonasal proportion and their comparisons in Bangladeshi Buddhist Rakhain Ethnic males and females.Methodology: This cross-sectional study was carried out in the Department of Anatomy, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh from January 2011 to December 2011 for a period of one (01) year. Adult healthy Bangladeshi Buddhist Rakhain males with the age group of 18 to 30 years were included as study population. Standard of normative facial anthropometric values related to intercanthal distance and nose width.Results: This study shows the inner intercanthal distance (IICD) mean value of males and females as 33.19±2.88 mm and 31.28±2.78 mm, respectively with a statistically significant relationship (P